New MoDC-Targeting TNF Fusion Proteins Enhance Cyclic Di-GMP Vaccine Adjuvanticity in Middle-Aged and Aged Mice - Gogoi, Himanshu; Mansouri, Samira; Katikaneni, Divya S.; Jin, Lei (Frontiers in Immunology, 2020)
Cyclic dinucleotides (CDNs) are promising vaccine adjuvants inducing balanced, potent humoral and cellular immune responses. How ageing influences CDNs' efficacy is unclear. We examined the vaccine efficacy of cyclic di-GMP (CDG), the founding member of CDNs, in 1-year-old (middle-aged), and 2-year-old (aged) C57BL/6J mice. We found that 1-year-old and 2-year-old C57BL/6J mice are defective in CDG-induced memory Th1 and Th17 responses and high-affinity serum IgG, mucosal IgA production. Next, we generated two novel TNF fusion proteins that target soluble TNF and transmembrane TNF to monocyte-derived DCs (moDCs) to enhance CDG vaccine efficacy in 1-year-old and 2-year-old mice. The moDCs-targeting TNF fusion proteins restored CDG-induced memory Th1, Th17, and high-affinity IgG, IgA responses in the 1-year-old and 2-year-old mice. Together, the data suggested that ageing negatively impacts CDG vaccine adjuvanticity. moDCs-targeting TNF fusion proteins enhanced CDG adjuvanticity in the ageing mice.